Platinum containing sensor nanomaterials based on tin dioxide to detect methane in air - Oleksenko, L.P.; Fedorenko, G.V.; Maksymovych, N.P.; Matushko, I.P. (Functional Materials, 2018)
Platinum-containing semiconductor materials on the base of nanosized SnO₂ (14 - 15 nm) were obtained using a sol-gel technology. Catalytic properties of these materials in the methane oxidation reaction and sensitivities to methane of the sensors with gas sensitive layer based on the obtained nanomaterials were studied. It was shown that properties of the sensors are determined by quantity of platinum introduced to semiconductor material and maxima of the sensor responses to methane are reached when 0.72 and 1.76 wt.% Pt are introduced. Created high sensitive adsorption-semiconductor sensors are stable and able to detect CH₄ in air in a wide range of its concentration.